Media Pembelajaran Online di Era Pandemi Covid-19, Mana yang Paling Efektif ? - Ismawati, Dwi; Afrodita, Meli; Sari, Dwi Lyna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study was to find out the effectiveness of these learning media and students' responses to learning in the Covid-19 pandemic era. The research method is descriptive with a survey approach. The instrument used was a questionnaire with a google form regarding the media used in the learning process during the Covid 19 Pandemic era. The technical data analysis used in this study was to count the number of respondents' answers from each port. The results of this study are that the learning media most used by lecturers and preferred is Google meet, the obstacles faced by students in daring learning are easily bored and difficult to understand the material, and student responses to learning from the Covid-19 Pandemic era are very happy. In conclusion, online learning media has its own advantages and disadvantages, but most prefer Google Meet as a learning medium, because it is easy to use, has complete learning features, is flexible and safer. Keywords: Covid-19 Pandemic, Learning Media, Effectiveness